Improving Habitat Quality at the Local and Landscape Scales Increases Wild Bee Assemblages and Associated Pollination Services in Apple Orchards in China - Wu, Panlong; Dai, Piaopiao; Wang, Meina; Feng, Sijie; Olhnuud, Aruhan; Xu, Huanli; Li, Xiang; Liu, Yunhui (Frontiers in Ecology and Evolution, 2021)
Bees provide key pollination services for a wide range of crops. Accumulating evidence shows the effect of semi-natural habitats at the landscape level and local management practices on bee diversity in fields. However, most of the evidence is derived from studies in North America and Europe. Whether this paradigm is applicable in China, which is characterized by smallholder-dominated agricultural landscapes, has rarely been studied. In this study, we aimed to investigate how bee diversity affected apple production, and how landscape and local variables affected bee diversity and species composition on the Northern China Plain. The results showed that bees significantly increased apple fruit set compared to bagged controls. Wild bee diversity was positively related to apple seed numbers. Higher seed numbers reduced the proportion of deformed apples and thus increased fruit quality. Wild bee abundance was positively correlated with flowering ground cover, and both the abundance and species richness of wild bees were positively affected by the percentage of semi-natural habitats. We conclude that apple quality can benefit from ecological intensification comprising the augmentation of wild bees by semi-natural habitats and flowering ground cover. Future pollination management should therefore reduce the intensification level of management at both the local and landscape scales.